Design of Fabrication-Tolerant and Compact Waveguide Superconducting Single-Photon Detector Based on TM0 Mode Absorption - Yang Li; Lue Tao; Yingxuan Zhao; Haiyang Huang; Xiaojuan She; Han Liao; Junbo Zhu; Zijian Zhu; Rui Huang; Xiang Liu; Fuwan Gan (IEEE Photonics Journal, 2021)
A TM0 mode coupled travelling wave SNSPD based on SOI platform is designed. The light propagating in this device can achieve high-efficiency mode conversion from TE0 mode to TM0 mode and then absorbed by NbN nanowires on top of the waveguide. Thanks to the TM0 mode coupled detection, the length of NbN nanowire that is needed to achieve a close-to-unity photon absorption is cut down to an extremely short level of ∼5 μm. Meanwhile, this TM0 mode coupled travelling wave SNSPD is very robust against fabrication errors compared with TE0 coupled SNSPD.